The role of core stability in surfing : According to a Delphi panel - Airaksinen, L. (2013)
Core stability has been widely discussed in physiotherapy. Yet, no consensus has been reached on the anatomy, tasks or benefits of core stability. Good core stability has been proven to decrease low-back pain and prevent specifically female athletes` from getting lower extremity injuries. Surfing has become an extremely popular sport. As a surfer I am intrigued to know what the exact role of core stability in surfing is. There are a limited number of studies on surfing and most of those concentrate on physiological aspects of the surfer. Thus a study was needed to determine the role of core stability in surfing. This thesis was executed with the Delphi technique via email. The expert panel, consisting of physiotherapists, answered questions related to surfing and the role core stability in surfing. An analysis was made and the results were summarised to generate new information on surfing and core stability from the physiotherapy point of view. The results are to be treated as guidelines as no measurements of the activity of core muscles were recorded. According to the results the role of core stability in surfing is extreme as it is present in almost all surfing manoeuvres. It is especially important in turns, where it is needed to control and project the forces that act on the body and thus enable the extremities to have a stable base to perform economical and precise movements. Good core stability ensures the correct alignment of the spine, which prevents and decreases the risk for injury. Surfers and their coaches emphasise core stability in addition to general physical and strength exercises to increase the surfer`s performance. According to this research, core stability exercises are vital in developing surfing performance.